Beneficiômetro da Seguridade Social: Uma introduç\~ao aos benefícios ofertados pela política de assistência social - Marina Brito Pinheiro; Claudia Baddini Curralero; Andrea Barreto de Paiva; Elaine Cristina Lício (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– This paper aims to carry out an exercise to measure the benefits of the social assistance policy, having as reference the conceptual framework of Ipea's Social Security Beneficiometer project (projeto Beneficiômetro da Seguridade Social do Instituto de Pesquisa Econômica Aplicada - Ipea). In addition, it aims to present the recent trajectory of the policy and unravel, as far as possible, some of its services and benefits. For this, a set of indicators was selected that attests to the scope of the social protection of assistance from the point of view of the diversity of social groups and situations of vulnerability for which programs, services and benefits are offered with the purpose of supporting the population in the search for a dignified life and resilience in the face of the risks to which they are exposed. The indicators have different degrees of complexity, but they aim to communicate in a relatively simple way what the social assistance policy does, particularly regarding non-monetary benefits, often intangible for those who are not beneficiaries or do not closely follow the implementation of the programs and services. It is hoped that the work can contribute to the dissemination of information and the articulation between the policies that make up the tripod of Brazilian social security and other social policies that go hand in hand in promoting the livelihood and quality of life of the Brazilian citizens.
Keywords: I38; 330; social protection; social assistance policy; social policies